Atomistic study of band structure and transport in extremely thin channel InP MOSFETs. Issue 4 (29th February 2016) - Dutta, Tapas; Kumar, Piyush; Rastogi, Priyank; Agarwal, Amit; Chauhan, Yogesh Singh
Abstract: Abstractauthoren III–V channel materials have emerged as one of the major contenders to replace silicon as the channel material in sub‐10 nm transistors. Motivated by this, we study the feasibility of using InP as a channel material in extremely scaled MOSFETs. In this work, we have performed a comprehensive analysis of the band structure of extremely thin InP channels with different surface orientations and transport directions using first‐principle density functional theory calculations. We show that the effective masses in the Γ valley and the bandgap increase monotonically as the thickness decreases for each orientation. Valley symmetry is found to be orientation dependent. Further, the performance of extremely thin InP channel double‐gate MOSFET is analyzed via semi‐classical as well as full quantum ballistic transport simulations using the non‐equilibrium Green's function (NEGF) approach.